WE5.6 Hajibandeh index is more accurate than NELA score in predicting mortality following emergency laparotomy in patients aged over 80. (9th August 2022) - Anwer, Amal Azhar; Hajibandeh, Shahab; Hajibandeh, Shahin; Waterman, Jennifer; Miller, Bethany; Evans, Louis; Maw, Andrew
Abstract: Aims: To compare performance of the Hajibandeh Index (HI) and National Emergency Laparotomy Audit (NELA) score in predicting mortality following emergency laparotomy (EL). Methods: In compliance with STROCSS guidelines for observational studies a cohort study was conducted. All patients who underwent EL between January 2014 and January 2021 in our centre were included. The performance of HI and NELA score in predicting 30-day and 90-day postoperative mortality were compared. The discrimination of each test was evaluated using ROC curve analysis, classification using classification table and calibration using a plotted diagram of the expected versus observed mortality rates. Results: Analysis of 700 patients showed that the predictive performance of the HI and NELA models were comparable (AUC: 0.86 vs 0.87, P=0.557). HI was significantly better than the NELA model in predicting postoperative mortality in patients aged over 80 (AUC: 0.85 vs 0.72, P=0.0174). The performances of both tools were comparable in patients with ASA status above 3 (AUC: 0.82 vs 0.82, P=0.9775), patients with intraperitoneal contamination (AUC: 0.77 vs 0.85, P=0.0728) and patients who needed a bowel resection (AUC: 0.85 vs 0.88, P=0.2749). Both tools were comparable in terms of classification and calibration. Conclusions: Hajibandeh index is better than the NELA score in predicting mortality following EL in patients aged over 80. Its performance is comparable to NELA for all patients, patients with ASA status above 3, patients with intraperitoneal contamination or patients who need a bowel resection. We encourage other researchers to validate HI in predicting mortality following EL.